Automated instrumentation for high-temperature Seebeck coefficient measurements. Issue 4 (4th July 2017) - Patel, Ashutosh; Pandey, Sudhir K.
ABSTRACT: The fabrication of automated instrumentation for high-temperature Seebeck coefficient measurements is presented. K-type thermocouples were used to measure the average temperature of the sample and the Seebeck voltage. The temperature dependence of the Seebeck coefficients of the thermocouple and its negative leg were obtained by the integration method. A steady-state-based differential technique was used for Seebeck coefficient measurement. The use of limited components and a thin heater simplified the sample holder design and minimized heat loss. The power supplied to the heater determined the temperature difference across the sample and the measurement was carried out by achieving a steady state. A LabVIEW-based program was constructed to automate the measurements. The complete setup was fabricated using commonly available materials. This instrument is standardized for materials with a wide range of Seebeck coefficients and temperature differences. High temperature measurements for iron, constantan, bismuth, and Bi 0.36 Sb 1.45 Te 3 were carried out and the results were in good agreement with standard values.